The University and social transformation in Algeria after Independence 1962-1989 - dahou, Umm Al-Khair; chetouah, Hakima (The Algerian Historical Journal, 2026)
In this paper, we will try to discuss the issue of higher education in the independent Algerian state, and the role of the university as an effective institution in national building, as it is responsible for producing competencies and knowledge that can drive development The authorities have given importance to the university and tried to involve it in the development project, but this role has extended to trying to contribute to political change.